Fatty acid methyl ester production from palm fatty acid distillate using sulfonated carbon-based catalyst from palm kernel shell and bamboo - Mohamad Saman, Ahmad Farabi (2018)
Excessive use of petroleum and concerns on the energy security along with the uncontrolled emission of greenhouse gases have made the world’s involuntarily to turn towards the utilization of environmental friendly and renewable biofuels. In this work, sulfonated carbon based solid acid catalysts were synthesized using two types of biomass sources which is from the palm kernel shell and bamboo. The catalysts were studied for its physico-chemical properties and applied as catalysts to convert the palm fatty acid distillate (PFAD) into fatty acid methyl esters (FAMEs). Solid acid catalysts prepared were derived from the palm kernel shell, bamboo and biochar. The sulfonated (-SO3H) group was attached on the surface of catalyst by hydrothermal process of carbon source with the chlorosulfonic acid (ClSO3H) under 70 °C for 4 hours with stirring rate of 500 rpm. Activated palm kernel shell was used in determining the optimum acid to biomass weight ratio for the sulfonation process. The resultant catalysts were characterized using X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray (SEM-EDX), thermogravimetric analysis (TGA), Brunauer-Emmett-Teller (BET), Fourier transform infrared (FTIR), temperature programed desorption (TPD-NH3). Meanwhile, the acid value for PFAD and percentage reduction of FFA were calculated using standard AOCS method (Cd 3d-63). From the characterization results, it was found that the carbon based catalysts (PKS, Bamboo and Biochar) have been successfully functionalized with –SO3H group that attached on the carbon structure. Different parameter (catalyst loading, methanol to oil ratio, reaction temperature and reaction time) was used in analyzing the performance of the prepared catalysts in assisting the esterification reaction of PFAD. The catalytic activity of PKSSO3H, Bamboo-SO3H and Biochar-SO3H demonstrated the highest conversion of PFAD to biodiesel under the following reaction condition: catalyst loading of 4 wt. %, methanol-to-PFAD molar ratio of 15:1, reaction temperature of 65 °C and the reaction time was 1 h. PKS-SO3H catalyst managed to produce the highest FAME yield and FFA conversion which is 95.1% and 97% respectively, meanwhile Bamboo-SO3H show the lowest FAME yield and FFA conversion which is 94.2% and 95.8% respectively. The catalysts can be reused for 4 cycles before complete deactivation of the catalytic active phase.